Heart rate variability, daily cortisol indices and their association with psychometric characteristics and gut microbiota composition in an Italian community sample - Sebastiano Ravenda; Leonardo Mancabelli; Sara Gambetta; Margherita Barbetti; Francesca Turroni; Luca Carnevali; Marco Ventura; Andrea Sgoifo (Scientific Reports)
Abstract The microbiota–gut–brain axis is a complex communication system that plays a crucial role in influencing various aspects of our physical and mental health. The goal of this study was to determine the extent to which individual differences in resting measures of vagally-mediated heart rate variability (HRV) and cortisol levels were associated with psychometric and specific gut microbiota characteristics in seventy-five (38 females) healthy individuals. Participants were assessed for vagally-mediated HRV, daily salivary cortisol levels, psychometric characteristics, and gut microbiota composition. Using a categorical approach based on the median split of HRV and cortisol values, we identified an association between low vagally-mediated HRV, greater depressive symptomatology, and altered gut microbiota (e.g., a higher abundance of Prevotella and a smaller abundance of Faecalibacterium, Alistipes, and Gemmiger). This suggests that vagally-mediated HRV may be a useful biomarker of microbiota-gut brain axis function, and that low vagally-mediated HRV may play an important role in the bidirectional link between gut dysbiosis and depression. On the other hand, daily cortisol parameters (e.g., cortisol awakening response, diurnal cortisol slope) were associated either with higher anxiety and perceived stress, or with a specific gut microbiota profile. Therefore, their utility as biomarkers of microbiota-gut-brain axis function needs further scrutiny.